Optimalisasi Potensi Lokal melalui Digital Marketing sebagai Strategi Meningkatkan Kemandirian Masyarakat di Dusun Kupo - Ariska, Denis; Lestari, Defitri Ayu; Setyawan, Danang; Aziz, Muhammad Abdul (Universitas Pahlawan Tuanku Tambusai, 2026)
This community service activity aims to increase the independence and empowerment of the Kupo Village community, Boyolali Regency, through the dissemination of digital marketing optimization for MSME actors in the copper and brass handicraft industry. MSMEs in rural areas still face a digital divide that causes limited market access and dependence on conventional marketing. Based on preliminary surveys and interviews, the main obstacle faced is a lack of digital technology knowledge. The activity began with a pre-test, interactive socialization on the importance of digital marketing and digital marketing optimization, and a post-test to measure the increase in understanding. The activity was attended by 20 participants aged 25–60 years, the majority of whom were housewives, with a high level of participation. The results of the activity showed an increase in participants' understanding of digital marketing, both theoretically and practically, such as content creation and social media promotion. This socialization was able to improve digital skills, confidence, and opportunities for increasing community income.Overall, this activity laid the foundation for a self-reliant digital economy and has the potential to be replicated in other rural areas to support sustainable development.